The Frequency of Intestinal Parasites in HIV Positive PatientsAdmitted To the Disease Consultation Center in Kermanshah Province. - H Taherkhani (Medical Laboratory Journal, 2007)
Abstract Background and objectives: Acquired immunodeficiency syndrome (AIDS) is acquired by infection with human immunodeficiency virus. (HIV).Parasite caused infection is the most common problem in AIDS Patients. Sometimes unusual and opportunistic infections such as intestinal parasitic infections may cause serious gastric intestinal (GI) disorders, which can finally lead to death. The aim of this study is to find intestinal parasites in AIDS patients referred to Disease Consultation Center of Kermanshah province. Materials and methods: In this study, the stool samples were collected from 75 AIDS patients admitted to Kermanshah consultation disease center. Then, all samples were tested by direct and formalin ether methods. Results: As shown in results , 13 patients (17.4%) are infected with Entamoeba coli, two( 2.7%) with Entamoeba histiolyticaly,one(1.4%) with Giardia lumbelia ,six (8%) with Blastocystis hominis ,two( 2.7%) with Isospora belli ,one(1.4%) with Ascaris lumbericoides ,two( 2.7%) with Endolimax nana . Conclusion: This study indicated that the frequency of pathogenic and non-pathogenic parasites was low in HIV+ patients. This may be related to anti-parasitic drugs used in all HIV+ patients admitted to Kermanshsh nsultation Disease center. Key words : Intestinal parasitic Infections, AIDS, Kermanshah consultation Disease center